The Simulation of Effect of MR Pulse Sequences on the Measurement Object Temperature - Kosková, Markéta (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
This paper deals with a heating tissues problem of the measured object in magnetic resonance. This is the consequence of using MRI pulse sequences. At the beginning of this paper is introduction to this topic and the ways of gathering the data necessary for the further processing. In experimental part of this paper the program for object heating simulation in MRI is proposed. This should help with planning the sequences so the researcher does not have to wait for the object to cool down, and also create the better conditions for the experimental animals to survive the process.
Keywords: nuclear magnetic resonance; tissue heating; graphical user interface